Aplikasi Mikroba Pelarut Fosfat dan Bahan Organik untuk Meningkatkan Serapan P dan Pertumbuhan Kentang Pada Andisol Terdampak Erupsi Gunung Sinabung - Susianti Susianti Marbun; Mariani Sembiring; Bintang Sitorus (Jurnal Agroekoteknologi, 2016)
Field study aimed to know the effect of P solubilizing microbe and organic matter application to P uptake and Potatos growth at Andisol impacted Sinabung Mountain eruption. The research was conducted in Kutarayat, Namanteran, regency of Karo. The research applied randomized block design factorial with two treatment factor and three replications. Microbe factor were control, P solubilizing bacterial (30 mL), P solubilizing fungi (30 mL), P solubilizing bacterial and fungi (15 mL + 15 mL) and organic matter factor were control, Cow feces organic matter (100 g/plant), chicken feces organic matter (100 g/plant), shaw organic matter (100 g/plant), Tithonia diversifolia (100 g/ plant). Parameter measured were soil pH, available-P, shoot dry weight and plant P uptake. The result showed that phosphate solubilizing fungi and cow feces or chicken feces organic matter aplication could increase P uptake and Potatos growth at Andisol impacted by Sinabung eruption.Keywords : Andisol, phosphate solubilizing microbe, organic matter, P uptake, potatos growthField study aimed to know the effect of P solubilizing microbe and organic matter application to P uptake and Potatos growth at Andisol impacted Sinabung Mountain eruption. The research was conducted in Kutarayat, Namanteran, regency of Karo. The research applied randomized block design factorial with two treatment factor and three replications. Microbe factor were control, P solubilizing bacterial (30 mL), P solubilizing fungi (30 mL), P solubilizing bacterial and fungi (15 mL + 15 mL) and organic matter factor were control, Cow feces organic matter (100 g/plant), chicken feces organic matter (100 g/plant), shaw organic matter (100 g/plant), Tithonia diversifolia (100 g/ plant). Parameter measured were soil pH, available-P, shoot dry weight and plant P uptake. The result showed that phosphate solubilizing fungi and cow feces or chicken feces organic matter aplication could increase P uptake and Potatos growth at Andisol impacted by Sinabung eruption.Keywords : Andisol, phosphate solubilizing microbe, organic matter, P uptake, potatos growth